2019
DOI: 10.3390/nu11102325
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Function in Gluten-Related Disorders

Abstract: Gluten-related disorders include distinct disease entities, namely celiac disease, wheat-associated allergy and non-celiac gluten/wheat sensitivity. Despite having in common the contact of the gastrointestinal mucosa with components of wheat and other cereals as a causative factor, these clinical entities have distinct pathophysiological pathways. In celiac disease, a T-cell mediate immune reaction triggered by gluten ingestion is central in the pathogenesis of the enteropathy, while wheat allergy develops as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 133 publications
0
65
0
1
Order By: Relevance
“…Recently, it was suggested that chronic disruptions in the functioning of the intestinal barrier can participate in the pathogenesis of several disorders, including autoimmune diseases [ 1 , 5 , 6 ]. In the altered barrier, non-competent intercellular junctions allow antigens derived from the food or intestinal microbiota to enter the internal milieu which challenges the immune system, resulting in the upregulated immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was suggested that chronic disruptions in the functioning of the intestinal barrier can participate in the pathogenesis of several disorders, including autoimmune diseases [ 1 , 5 , 6 ]. In the altered barrier, non-competent intercellular junctions allow antigens derived from the food or intestinal microbiota to enter the internal milieu which challenges the immune system, resulting in the upregulated immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the barrier function is maintained by a protein-protein complex interaction, where the main structure is the tight junction (TJ) proteins. TJs are the most apical contact between enterocytes formed by integral membrane proteins, including occludin, claudins, and scaffolding proteins as ZO-1 [6]. Although structural changes in celiac barrier function can be allocated to enterocyte TJ composition and epithelial transcytosis of gliadin peptides, research aiming to clarify how these changes arise is scarce [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has suggested that, despite a lifelong gluten-free diet, some disorders can persist, e.g., increased gut permeability, small bowel overgrowth, microbiota changes, exocrine pancreatic insufficiency, and low-grade gastrointestinal inflammation [46][47][48][49]. Some of these disorders could be responsible for the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%